2022
DOI: 10.1007/s10461-022-03592-x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Oral Pre-exposure Prophylaxis (PrEP) Continuation Among Women from Durban, South Africa, Who Initiated PrEP as Standard of Care for HIV Prevention in a Clinical Trial

Abstract: HIV incidence among women in Eastern and Southern Africa remains unacceptably high, highlighting the need for effective HIV prevention options, including pre-exposure prophylaxis (PrEP). The Evidence for Contraceptive Options and HIV Outcomes trial offered daily oral PrEP to participants during the latter part of the clinical trial as an additional HIV prevention choice. We explored daily oral PrEP continuation at trial exit among women enrolled from Durban, South Africa who initiated oral PrEP at the trial si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Behavioral economic theories have shown that individuals tend to make decisions based on information received more recently, 28 and although this effect might have been beneficial to get women initiated on PrEP, it may have biased women against fully considering the implications and demands of PrEP continuation. This finding supports several studies that show that barriers to PrEP initiation are different to barriers to PrEP continuation, [29][30][31] and suggest that, although POC STI testing might improve PrEP initiation in PPW, PrEP adherence and continuation counseling is critical to improve long-term outcomes in this population. This study did not include a biomarker for PrEP adherence and relied on self-report and pill count, which is an imperfect measure of PrEP adherence.…”
Section: Discussionsupporting
confidence: 89%
“…Behavioral economic theories have shown that individuals tend to make decisions based on information received more recently, 28 and although this effect might have been beneficial to get women initiated on PrEP, it may have biased women against fully considering the implications and demands of PrEP continuation. This finding supports several studies that show that barriers to PrEP initiation are different to barriers to PrEP continuation, [29][30][31] and suggest that, although POC STI testing might improve PrEP initiation in PPW, PrEP adherence and continuation counseling is critical to improve long-term outcomes in this population. This study did not include a biomarker for PrEP adherence and relied on self-report and pill count, which is an imperfect measure of PrEP adherence.…”
Section: Discussionsupporting
confidence: 89%
“…In mainland China, for example, the cost of daily oral PrEP is around CNY 780–2000 (USD 111–285) per month. Another reason for poor uptake is concern about adverse effects of PrEP such as nausea, vomiting, and abdominal pain [ 67 ]. Someone concerned about adverse effects is unlikely to take action to use PrEP, since like all medications, PrEP may cause side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In mainland China, for example, the cost of daily oral PrEP is around CNY 780-2000 (USD 111-285) per month. Another reason for poor uptake is concern about adverse effects of PrEP such as nausea, vomiting, and abdominal pain [49]. Furthermore, due to traditional cultural beliefs about medicine, it is widely acknowledged in China that all drugs have some toxicity and that individuals are unwilling to take medicine until they have symptoms, which also acts as a roadblock to PrEP uptake among MSM at high risk of HIV infection [50].…”
Section: Discussionmentioning
confidence: 99%